Development and Preliminary Psychometric Evaluation of Decisional Balance and Self-Efficacy Measures for Managing Anxiety in a National Sample of Clinically Anxious Adults. Issue 1 (January 2018) - Lipschitz, Jessica M.; Paiva, Andrea L.; Redding, Colleen A.; Levesque, Deborah; Rossi, Joseph S.; Weisberg, Risa B.; Prochaska, James O.
Purpose: Anxiety is the most common and costly mental illness in the United States. Reducing avoidance is a core element of evidence-based treatments. Past research shows readiness to address avoidance affects outcomes. Investigating avoidance from a transtheoretical model (TTM) perspective could facilitate tailored approaches for individuals with low readiness. This study developed and examined psychometric properties of TTM measures for addressing anxiety-based avoidance. Design: Cross-sectional survey. Setting: Community centers, online survey. Participants: Five hundred ninety-four individuals aged 18 to 70 with clinically significant anxiety. Measures: Overall Anxiety Severity Questionnaire, stages of change, decisional balance, and self-efficacy. Analysis: The sample was randomly split into halves for principal component analyses (PCAs) and confirmatory factor analyses (CFAs) to test measurement models. Further analyses examined relationships between constructs. Results: For decisional balance, PCA indicated two 5-item factors (pros and cons). Confirmatory factor analysis supported a 2-factor correlated model, Satorra-Bentler scaled chi-square( χ SB 2 [ 35 ] = 80.82 ), comparative fit index (CFI = 0.94), root mean square error of approximation (RMSEA = 0.07), pros: α = 0.87, ρ = 0.87, cons: α = 0.75, and ρ = 0.75. For self-efficacy, PCA indicated one 6-item factor supported by CFA, χ SB 2 ( 9 ) = 30.39, P < .01, CFI = 0.98, RMSEA = 0.09, α = 0.90, ρ = 0.87. As hypothesized, significant cross-stage differences were observed for pros and self-efficacy, and significant relationships between anxiety severity and pros, cons, and self-efficacy were found. Conclusion: Findings show strong psychometric properties and support the application of a readiness-based model to anxiety. In contrast to findings of other behaviors, cons remain high in action and maintenance. These measures provide a solid empirical foundation to develop TTM-tailored interventions to enhance engagement in treatment.